STRATEGI KSPPS BAYTUL IKHTIAR CABANG PAMIJAHAN BOGOR DALAM MENGEMBANGKAN USAHA MIKRO KECIL DAN MENENGAH PADA MASA COVID-19 - Oktavia, Siska; Trihantana, Rully; Kusumaningrum, Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
MSME actors in KSPPS Baytul Ikhtiar Pamijahan Branch have so far experienced difficulties in developing their business, so research is needed to find out the condition of MSMEs and how KSPPS Baytul Ikhtiar Pamijahan branch develops business strategies with MSME business actors in the midst of conditions where some members experience bad financing due to reduced member income during the Covid-19 pandemic. The research conducted was field research with a descriptive qualitative approach. The subject of this research is the KSPPS Baytul Ikhtiar Pamijahan Branch. The data collection technique used is by using Observation, Interview and Documentation methods. The data analysis used is using data obtained from interviews, observation and documentation, by collecting, describing, and shaping it in a SWOT analysis. The research results obtained are the strategy carried out by KSPPS Baytul Ikhtiar in developing MSMEs, namely the mentoring strategy. Where MSME actors who were given financing were surveyed directly in the field to see the development of MSMEs and provide direction and motivation to improve business quality. With this assistance, MSME actors can foster good MSME management and good marketing, can increase and expedite MSME income. Such assistance as assistance in managing funds, assistance in financial management for the sustainability of MSMES.